2017
DOI: 10.1177/0194599817719400
|View full text |Cite
|
Sign up to set email alerts
|

Critical Airway Team: A Retrospective Study of an Airway Response System in a Pediatric Hospital

Abstract: Objective Study the performance of a pediatric critical airway response team. Study Design Case series with chart review. Setting Freestanding academic children's hospital. Subjects and Methods A structured review of the electronic medical record was conducted for all activations of the critical airway team. Characteristics of the activations and patients are reported using descriptive statistics. Activation of the critical airway team occurred 196 times in 46 months (March 2012 to December 2015); complete dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 30 publications
7
23
0
Order By: Relevance
“…Interestingly, genetic syndromes without craniofacial involvement did not increase the risk for DART intervention, nor did airway bleeding or musculoskeletal diseases. Similar to results published by Sterrett et al [9], we found that intubation by both the DART and RRT occurred throughout all hours of the day and night. Not only must hospitals have RRTs staffed with expert personnel, these teams must also be readily available 24 hours a day.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, genetic syndromes without craniofacial involvement did not increase the risk for DART intervention, nor did airway bleeding or musculoskeletal diseases. Similar to results published by Sterrett et al [9], we found that intubation by both the DART and RRT occurred throughout all hours of the day and night. Not only must hospitals have RRTs staffed with expert personnel, these teams must also be readily available 24 hours a day.…”
Section: Discussionsupporting
confidence: 91%
“…Patients with craniofacial abnormalities or airway swelling, or who were 1-2 years old, were significantly more likely to have airway management by the DART in our study than were children without these risk factors. These findings are consistent with previously identified risk factors for difficult airway management in children [3,9,10]. Unexpectedly, active chest compressions were more common during intubations performed by the RRT, suggesting that glottic movement did not contribute to the ease of endotracheal tube placement.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, nine patients (i.e., 2.5% of the cases needed intubation by the AC team) required an additional ENT airway call for securing a surgical airway, similar to a report from a 628-bed pediatric hospital (2.5% of 162 activations), 16 but much higher than that of another hospital (0.26% of 3,423 activations). 2 …”
Section: Discussionsupporting
confidence: 88%
“…There were no claims of malpractice, death, or morbidity lodged for adult patients with DART involvement. Programs similar to the DART have now been successfully implemented outside of Johns Hopkins including in pediatric hospitals [54][55][56][57][58].…”
Section: Airway Leads and Airway Response Teamsmentioning
confidence: 99%